2017
DOI: 10.1186/s12889-017-4120-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening, prevalence, and risk factors for cervical lesions among HIV positive and HIV negative women in Swaziland

Abstract: BackgroundCervical Cancer (CC) is the number one cancer among women in sub-Saharan Africa. Although CC is preventable, most women in developing countries do not have access to screening.MethodsThis cross-sectional study was conducted to determine the prevalence and risk factors for cervical lesions using visual inspection with acetic acid (VIA) among 112 HIV positive and 161 negative women aged 18–69 years.ResultsThe presence of cervical lesions was greater among HIV positive (22.9%) than HIV negative women (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 16 publications
19
47
1
Order By: Relevance
“…To our knowledge, no previous study on predictors of VIA positivity has assessed the mutually adjusted effect of HrHPV and HIV. In accordance with our findings, some recent cross‐sectional studies from developing African countries have reported increased risk of VIA positivity among HIV‐positive women . Only few studies have assessed HrHPV as a risk factor for VIA positivity.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, no previous study on predictors of VIA positivity has assessed the mutually adjusted effect of HrHPV and HIV. In accordance with our findings, some recent cross‐sectional studies from developing African countries have reported increased risk of VIA positivity among HIV‐positive women . Only few studies have assessed HrHPV as a risk factor for VIA positivity.…”
Section: Discussionsupporting
confidence: 92%
“…Women who had multiple sexual partners in their lifetime were 2.67 times more likely to have the precancerous lesion of the cervix than those who had no multiple sexual partners. This is in line with studies done in Côte D’Ivoire [ 43 ], Swaziland [ 44 ], Kenya [ 45 ], united states [ 46 ], Italy [ 47 ], and Tanzania [ 48 ]. Women having multiple sexual partners may be exposed to factors predisposing to the precancerous lesions of the cervix such as HIV and STI.…”
Section: Discussionsupporting
confidence: 90%
“…Liu, et al 24 reported that number of partners was highly associated with cervical cancer from the meta-analysis. Whereas several studies [25][26][27] reported that women's number of partners and history of STIs were associated with cervical cancer among the women in South Africa. However, the study of Obiri-Yeboah 28 reported that age of women and circumcision status of main sexual partner were associated with cervical cancer, but no association was found with number of partners.…”
Section: Discussionmentioning
confidence: 99%